Fusarinine C, a novel siderophore‐based bifunctional chelator for radiolabeling with Gallium‐68 - Zhai, Chuangyan (J Labelled Comp Radiopharm, 2015)
Fusarinine C (FSC), a siderophore‐based chelator coupled with the model peptide c(RGDfK) (FSC(succ‐RGD)(3)), revealed excellent targeting properties in vivo using positron emission tomography (PET). Here, we report the details of radiolabeling conditions and specific activity as well as selectivity for (68)Ga. (68)Ga labeling of FSC(succ‐RGD)(3) was optimized regarding peptide concentration, pH, temperature, reaction time, and buffer system. Specific activity (SA) of [(68)Ga]FSC(succ‐RGD)(3) was compared with (68)Ga‐1,4,7‐triazacyclononane, 1‐glutaric acid‐4,7 acetic acid RGD ([(68)Ga]NODAGA‐RGD). Stability was evaluated in 1000‐fold ethylenediaminetetraacetic acid (EDTA) solution (pH 7) and phosphate‐buffered saline (PBS). Metal competition tests (Fe, Cu, Zn, Al, and Ni) were carried out using [(68)Ga]‐triacetylfusarinine C. High radiochemical yield was achieved within 5 min at room temperature, in particular allowing labeling with (68)Ga up to pH 8 with excellent stability in 1000‐fold EDTA solution and PBS. The 10‐fold to 20‐fold lower concentrations of FSC(succ‐RGD)(3) led to the same radiochemical yield compared with [(68)Ga]NODAGA‐RGD with SA up to 1.8 TBq/µmol. Metal competition tests showed high selective binding of (68)Ga to FSC. FSC is a multivalent siderophore‐based bifunctional chelator allowing fast and highly selective labeling with (68)Ga in a wide pH range and results in stable complexes with high SA. Thus it is exceptionally well suited for the development of new (68)Ga‐tracers for in vivo molecular imaging with PET.